Deferoxamine therapy for intracerebral hemorrhage: A systematic review. - Liling Zeng; Li Tan; Haijun Li; Qixin Zhang; Yongxian Li; Jianwen Guo (PLoS ONE, 2018)
Intracerebral hemorrhage (ICH) is a significant cause of morbidity and mortality worldwide. Several recent controlled trials have reported that deferoxamine (DFX) therapy appears to be effective for ICH. The aim of this study was to perform a systematic review of DFX therapy for ICH patients and evaluate the efficacy and safety of DFX therapy for ICH patients. We searched Medline, Embase, the Cochrane Database of Systematic Reviews, clinicaltrials.gov, all Chinese databases and the reference lists of all included studies and review articles. We then performed a systematic review of studies involving the administration of DFX following ICH. Only two studies were included, a prospective, randomized clinical trial and a prospective,observational cohort study with concurrent groups. Qualitative analysis of each study revealed one randomized controlled trial of moderate quality with a moderate risk of bias and one observational cohort study of moderate quality with a moderate risk of bias. DFX may be an effective treatment for edema in patients with ICH. However, due to the small number of trials and small sample sizes of these trials, insufficient evidence exists to determine the effect of DFX on neurologic outcomes after ICH and the safety of this intervention. Further investigation is required before DFX can become a routine treatment for ICH.